Chemistry laboratory management in senior high schools: a competency analysis - Sartika, Rody Putra; Maisyaroh, Maisyaroh; Timan, Agus; Juharyanto, Juharyanto (Intelektual Pustaka Media Utama, 2025)
Laboratory management is crucial in improving the quality of chemistry learning in senior high schools. However, there has been limited research on the managerial competence of chemistry teachers in managing laboratories. This study aims to analyze the managerial competence of high school chemistry teachers in laboratory management. The study used a survey method with non-probability sampling and involved 99 high school chemistry teachers from 476 high schools in West Kalimantan Province. The results showed that the average managerial competence of these teachers was only 16.26%. Further analysis revealed that teachers' competencies in planning (19.19%), organizing (2.53%), implementing (28.08%), controlling (22.89%), and evaluating (7.32%) were significantly lacking. The findings highlight the need to improve the managerial competencies of chemistry teachers in this region. This study provides a foundation for developing a chemistry laboratory management model to enhance these competencies, contributing to better implementation of experiments and improved quality of chemistry learning in high schools.